1984
DOI: 10.1021/bi00320a004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of protein salting in and salting out by divalent cation salts: balance between hydration and salt binding

Abstract: The preferential interactions of proteins with solvent components were studied in concentrated aqueous solutions of the sulfate, acetate, and chloride salts of Mg2+, Ba2+, Ca2+, Mn2+ and Ni2+ [except for CaSO4, BaSO4, Mn-(OAc)2, and Ni(OAc)2], and results were compared with those of the Na+ salts. It was found that, for all the salts, the preferential hydration increased in the order of Cl- less than CH3-COO- less than SO42- regardless of the cationic species used, in agreement with the anionic lyotropic serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
400
2
6

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 625 publications
(436 citation statements)
references
References 33 publications
24
400
2
6
Order By: Relevance
“…This is done by multiplying the calculated value of (apz/am3);,,,, by the ratio, R , of the experimental to the calculated value determined for systems that show no evidence of binding. In previous studies, it has been shown that R has values between 0.5 and 0.7 (Arakawa & Timasheff, 1982a, 1983, 1984b, which are similar to those calculated by Honig and co-workers from geometric considerations Sharp et al, 1991). Therefore, for consistency, all the preferential interaction parameters calculated with the Gibbs adsorption isotherm were corrected by this factor.…”
Section: Separation Of the Measured Preferential Exclusion Into Contrsupporting
confidence: 58%
See 1 more Smart Citation
“…This is done by multiplying the calculated value of (apz/am3);,,,, by the ratio, R , of the experimental to the calculated value determined for systems that show no evidence of binding. In previous studies, it has been shown that R has values between 0.5 and 0.7 (Arakawa & Timasheff, 1982a, 1983, 1984b, which are similar to those calculated by Honig and co-workers from geometric considerations Sharp et al, 1991). Therefore, for consistency, all the preferential interaction parameters calculated with the Gibbs adsorption isotherm were corrected by this factor.…”
Section: Separation Of the Measured Preferential Exclusion Into Contrsupporting
confidence: 58%
“…All of these co-solvents raise the surface tension of water. The good correlation between the measured negative preferential interactions and the positive surface tension increment in their presence (Arakawa & Timasheff, 1982a, 1982b, 1983, 1984bKita et al, 1994) led to the proposal that this is the principal source of the unfavorable free energy of the interactions of these co-solvents with proteins. These observations have suggested that the stabilization of proteins by these co-solvents is due to the increase of the surface tension in their presence.…”
mentioning
confidence: 99%
“…This behavior is observed with other molecules such as ionic liquids 79 and proteins. 43,57 However, the solubility effects observed with the amino acids studied here are the opposite. The Mg 2+ cation seems to be a strong salting-in agent, in good agreement with its "chaotropic" character described for other biomolecules such as polymers, 80 charged polypeptides 45 and some amino acids.…”
Section: Methodsmentioning
confidence: 72%
“…On the other hand, the D fraction in Timasheff, 1984;Timasheff, 1992Timasheff, , 1993. In the lower concentration range of (NH4)?SO, (typically < O S M), the salting-in effect is superior to the preferential hydration effect, often resulting in destabilization of the folded state of proteins.…”
Section: Some Results In Water and Co-solvent Solutionsmentioning
confidence: 99%